2020
DOI: 10.1002/hbm.25169
|View full text |Cite
|
Sign up to set email alerts
|

Distinct influence of parental occupation on cortical thickness and surface area in children and adolescents: Relation to self‐esteem

Abstract: Studies of socioeconomic disparities have largely focused on correlating brain measures with either composite measure of socioeconomic status (SES), or its components-family income or parental education, giving little attention to the component of parental occupation. Emerging evidence suggests that parental occupation may be an important and neglected indicator of childhood and adolescent SES compared to absolute measures of material resources or academic attainment because, while related, it may more precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
0
15
1
Order By: Relevance
“…For example, it was found in a previous study that those from families with higher levels of parental occupation (titles falling into the category of "higher executives of large concerns, proprietors, and major professionals") were shown to have larger cortical surface areas than those from families with lower levels of parental occupation (titles falling into the category of unskilled laborers). 38 Likewise, one of our previous studies found that a higher level of parental education is positively associated with increased cortical surface areas and higher reading levels among children. 24 This occurrence is due to the distal effects that SES has on environments surrounding a child.…”
Section: Discussionmentioning
confidence: 76%
“…For example, it was found in a previous study that those from families with higher levels of parental occupation (titles falling into the category of "higher executives of large concerns, proprietors, and major professionals") were shown to have larger cortical surface areas than those from families with lower levels of parental occupation (titles falling into the category of unskilled laborers). 38 Likewise, one of our previous studies found that a higher level of parental education is positively associated with increased cortical surface areas and higher reading levels among children. 24 This occurrence is due to the distal effects that SES has on environments surrounding a child.…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, several studies focussed on the role that parents play in children's development of numerical competencies [16][17][18]. Here, studies differ in their usage of various SES measures [10,19], and the most common aspects (i.e., parental occupation, education, and income) seem to be highly correlated [20,21].…”
Section: Parental Occupation and Other Aspects Of Socioeconomic Statusmentioning
confidence: 99%
“…Here, the SES can be conceptualized as a multidimensional construct that acts as an indicator of a family's economic and social resources. SES is mostly measured with three objective parental factors: income, occupation, and education [10]. In addition, neighbourhood, social standing, and prestige are often considered as SES estimates as well [1,10].…”
Section: Introduction 1family's Socioeconomic Status and Children's Early Numerical Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw T1-weighted imaging data for the PING study are publicly shared (https://nda.nih.gov/) for a subset of the sample (n = 934). The only difference between the full PING sample and the subsample with raw T1-weighted imaging data was that the full PING sample was older on average than the subsample (Khundrakpam, Choudhury, et al, 2020). We used the CIVET processing pipeline (https://mcin.ca/technology/civet/) developed at the Montreal Neurological Institute to compute CT measurements at 81,924 regions covering the entire cortex.…”
Section: Image Acquisition and Preprocessingmentioning
confidence: 99%